Evaluation of Health in Pregnancy grants in Scotland: a natural experiment using routine data - Alastair H Leyland; Samiratou Ouédraogo; Julian Nam; Lyndal Bond; Andrew H Briggs; Ron Gray; Rachael Wood; Ruth Dundas (NIHR Journals Library, 2017)
Background: Pregnancy and the period around birth are critical for the development and improvement of population health as well as the health of mothers and babies, with outcomes such as birthweight influencing adult health. Objectives: We evaluated the clinical effectiveness and cost-effectiveness of the Health in Pregnancy (HiP) grants in Scotland, looking for differential outcomes when the scheme was in place, as well as before its implementation and after its withdrawal. Design: The HiP grants were evaluated as a natural experiment using interrupted time series analysis. We had comparison groups of women who delivered before the grants were introduced and after the grants were withdrawn. Setting: Scotland, UK. Participants: A total of 525,400 singleton births delivered between 24 and 44 weeks in hospitals across Scotland between 1 January 2004 and 31 December 2014. Intervention: The HiP grant was a universal, unconditional cash transfer of £190 for women in Great Britain and Northern Ireland reaching 25 weeks of pregnancy if they had sought health advice from a doctor or midwife. The grant was introduced for women with a due date on or after 6 April 2009 and subsequently withdrawn for women reaching the 25th week of pregnancy on or after 1 January 2011. The programme was paid for by Her Majesty's Treasury. Main outcome measures: Our primary outcome measure was birthweight. Secondary outcome measures included maternal behaviour, measures of size, measures of stage and birth outcomes. Data sources: The data came from the Scottish maternity and neonatal database held by the Information and Services Division at the NHS National Services Scotland. Results: There was no statistically significant effect on birthweight, with births during the intervention period being, on average, 2.3 g [95% confidence interval (CI) -1.9  to 6.6 g] lighter than would have been expected had the pre-intervention trend continued. Mean gestational age at booking (i.e. the first antenatal appointment with a health-care professional) decreased by 0.35 weeks (95% CI 0.29 to 0.41 weeks) and the odds of booking before 25 weeks increased by 10% [odds ratio (OR) 1.10, 95% CI 1.02 to 1.18] during the intervention but decreased again post intervention (OR 0.91, 95% CI 0.83 to 1.00). The odds of neonatal death increased by 84% (OR 1.84, 95% CI 1.22 to 2.78) and the odds of having an emergency caesarean section increased by 7% (OR 1.07, 95% CI 1.03 to 1.10) during the intervention period. Conclusions: The decrease in the odds of booking before 25 weeks following withdrawal of the intervention makes it likely that the HiP grants influenced maternal health-care-seeking behaviour. It is unclear why neonatal mortality and emergency caesarean section rates increased, but plausible explanations include the effects of the swine flu outbreak in 2009 and the global financial crisis. The study is limited by its non-randomised design. Future research could assess an eligibility threshold for payment earlier than the 25th week of pregnancy. Funding: The National Institute for Health Research Public Health Research programme. The Social and Public Health Sciences Unit is core funded by the Medical Research Council (MC_UU_12017/13) and the Scottish Government Chief Scientist Office (SPHSU13).